The Influence of Service Systems and Library Spatial Aesthetics at UIN Ponorogo on Visiting Interest - Ummah, Salwa Zahrotul; Lathifunisa, Hilwa Sifa’ulia; Nisak, Khoirun; Junaidi, Muhammat; Naifa, Rena Fauzan; Wulandari, Wanda Tri; Kardi, Kardi (Lentera Pustaka: Jurnal Kajian Ilmu Perpustakaan, Informasi dan Kearsipan, 2025)
Background: Libraries play an important role in the teaching and learning process, especially in the realm of higher education. Generally, university libraries have complete facilities, but there are still minimal visitors. The lack of interest in visiting students in university libraries may be caused by factors in the library service system, including less friendly staff services or less aesthetic library layout. The research background starts from the condition of the UIN Ponorogo library which has minimal student visits, even though it has thousands of students.Objective: This study aims to determine the significant influence between independent variables (service system and aesthetics of library spatial layout) and bound variables (interest in visiting students of the Department of Islamic Education Management semester 4, Faculty of Tarbiyah and Teacher Training UIN Ponorogo.Methods: This study uses quantitative and observational methods, sampling through non-probability sampling techniques with a sampling quota of 30 Islamic Education Management students in the 4th semester. Data collection through a questionnaire via google form, with a Likert scale. The analysis method used multiple linear regression analysis. Observation was carried out by directly observing the condition of the UIN Ponorogo library and analyzing library visit data.Conclusion: The results showed that the service system had a positive and insignificant effect on visitor interest, while spatial aesthetics had a positive and significant effect on visitor interest at a significance level of 5%. Simultaneously, the two variables had a positive and significant influence on visitor interest at a significance level of 5%. The service system contributed 6% and spatial aesthetics 20% to the interest of visitors, with a total donation of 26%. Thus, both variables had moderate influence, with 74% coming from other factors outside the study.